Text & Talk : An Interdisciplinary Journal of Language, Discourse & Communication Studies (De Gruyter Mouton, 1981)
Text & Talk (founded as TEXT in 1981) is an internationally recognized forum for interdisciplinary research in language, discourse, and communication studies, focusing, among other things, on the situational and historical nature of text/talk production; the cognitive and sociocultural processes of language practice/action; and participant-based structures of meaning negotiation and multimodal alignment.